Iconographic Program of Altar Murals in the Smolensk Cathedral of the Novodevichy Convent and Piety of the Godunov Family - Preobrazhenskii, Aleksandr S. (Actual Problems of Theory and History of Art, 2023)
The Church of the Smolensk icon of the Virgin in the Novodevichy Convent in Moscow was painted in the late 1590s, immediately after Tsar Boris Godunov’s accession to the throne. This is a most important monument of capital art from the time of Boris, undoubtedly created with the direct participation of the royal donor. Although the iconographic program of this ensemble has already been discussed in a number of studies, it has been explored unevenly. In particular, the interpretation of compositions in the altar space — the central apse and the eastern arm of the cross — remains insufficiently complete. Their analysis convinces that the paintings of these compartments are the most important element of the complex. The figures of the heavenly patrons of the Godunov family, including the Dowager Tsarina Irina, her late husband Tsar Fyodor and their daughter Theodosia, who died in infancy, standing before the image of the Mother of God Hodegetria of Smolensk, make up a ktetor composition that replaces portraits of donors, almost unacceptable for the Muscovite culture of that time. They testify to the desire to legitimize the new dynasty. Located in the area of the altar vault, the saints of the Godunov family are elevated into heavenly space, but are visually removed from those praying in naos so that the privileged position of the members of the new reigning family is not so noticeable. The theme of salvation and unity with the heavenly world is more openly expressed in the scene “The Intercession (Pokrov) of the Mother of God,” placed in the apse conch. This is an image of the Orthodox kingdom finding salvation in the bosom of the Church under the auspices of the Intercessor Mother of God. Separated by the iconostasis, but located opposite, on the eastern surfaces of the western dome pillars, the symbolic images of the Mother of God with Christ in the tomb and the “Savior Anapeson”, are semantically combined with the altar painting. Both compositions are related to the theme of the Savior’s Sabbath dream, which will be immediately followed by the Resurrection and the deliverance of humanity from the power of death. The “Protection of the Mother of God” in the conch personifies this ideal state of the universe on the threshold of the Kingdom of Heaven. Since the painting of the church does not contain a scene of the Last Judgment, it can be assumed that the construction of such an optimistic picture not only corresponded to the contemplative piety of Godunov’s era, but also expressed Tsar Boris’s own hopes for a quiet and serene reign, or even served as a promise of such a reign on his part.